A comparative study of the vocal parameters between hypofunctional and hyperfunctional dysphonia using perceptual and cepstral spectral index of dysphonia measures - Goswami, Debaruna; Chatterjee, Indranil; Samaddar, Pamela; Narayanan, Shalini S.; Saha, Arup; Basu, Tulika (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: The main goal of the present study was to obtain the cepstral spectral index of dysphonia (CSID) scores for normophonic, hypo-functional dysphonic and hyper-functional dysphonic Indian population along with correlation of CSID and GRBAS scores for normophonic, hypo-functional dysphonic and hyper-functional dysphonic population using sustained production of vowel and oral passage of Bengali language. Methods: A total of 60 participants between 20-50 years were selected for the study. The participants were divided into three groups viz., 30 normal subjects, 15 subjects with hypofunctional dysphonia and 15 subjects with hyperfunctional dysphonia. The subjects were screened for speech and hearing defects. Recordings of sustained vowels and passage were done and then fed to measure CSID through PRAAT and software developed by C-DAC. Statistical analyses were done for the analyzed data using SPSS. Results: Significant differences (p<0.05) were found in CSID scores across hypofunctional dysphonia group and hyperfunctional dysphonia group when compared to normophonia group. There were no significant differences (p>0.05) between hypofunctional and hyperfunctional dysphonia group in CSID score. A significantly strong correlation of CSID scores with the ‘G’ rating of GRBAS scores (p<0.01) were found for both hypofunctional dysphonia and hyperfunctional dysphonia groups. ROC analysis showed high sensitivity and specificity of CSID scores in two dysphonia groups with respect to normophonia group. Conclusions: The current study revealed significant differences obtained in CSID scores across normophonia, hypofunctional dysphonia and hyperfunctional dysphonia groups suggesting it as assessment tool to determine the presence of dysphonia.